1992
DOI: 10.1128/aem.58.4.1392-1393.1992
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Reductive Dechlorination of Tetrachloroethene in Anaerobic Aquifer Microcosms by Addition of Short-Chain Organic Acids or Alcohols

Abstract: The effect of the addition of common fermentation products on the dehalogenation of tetrachloroethene was studied in methanogenic slurries made with aquifer solids. Lactate, propionate, crotonate, butyrate, and ethanol stimulated dehalogenation activity, while acetate, methanol, and isopropanol did not. Although the ecological and public health risks associated with tetrachloroethene (PCE) contamination may be the most severe when spills affect groundwater, little is known about the environmental conditions ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 14 publications
2
43
0
3
Order By: Relevance
“…For recent reviews on anaerobic dehalogenating bacteria, the reader is referred to Smidt and de Vos (2004) and Bradley (2003). Although some dehalogenating bacteria can use organic substrates as electron donors, molecular hydrogen (H 2 ) seems to be the major electron donor for dehalogenation of chlorinated compounds in mixed microbial communities (Distefano et al ., 1992;Gibson and Sewell, 1992;Luijten et al ., 2004a). Most dehalogenating bacteria, e.g.…”
Section: Exocellular Electron Transfer In Methanogenic Environmentsmentioning
confidence: 99%
“…For recent reviews on anaerobic dehalogenating bacteria, the reader is referred to Smidt and de Vos (2004) and Bradley (2003). Although some dehalogenating bacteria can use organic substrates as electron donors, molecular hydrogen (H 2 ) seems to be the major electron donor for dehalogenation of chlorinated compounds in mixed microbial communities (Distefano et al ., 1992;Gibson and Sewell, 1992;Luijten et al ., 2004a). Most dehalogenating bacteria, e.g.…”
Section: Exocellular Electron Transfer In Methanogenic Environmentsmentioning
confidence: 99%
“…Trichloroethene (TCE) is a common groundwater contaminant in aquifers throughout the United States (Westrick et al, 1984).TCE ranks in the top ten priority pollutants listed by the U.S. Environmental Protection Agency (EPA) (Federal Register, 1989). Over the past decade, microbial degradation of TCE has been extensively studied (Hopkins et al, 1993;Mars et al, 1996;Alvarez-Cohen & McCarty, 1991;Gibson & Sewell, 1992;Maymo-Gatell et al, 1997;Distefano et al, 1992;Fennell et al, 1997;Smatlak et al, 1996;Ballapragada et al, 1997;Sharma & McCarty, 1996;Semprini et al, 1995). Reductive dechlorination under anaerobic conditions and aerobic cometabolic processes are the predominant pathways for TCE transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Field and laboratory evidences depicted that the addition of auxiliary carbon and energy sources (electron donor) is necessary for microorganisms for the onset of the dechlorination of tracelevel organic compounds. Gibson and Sewell (1992) examined the effect of short-chain organic acids and alcohols on the dechlorination of PCE with anaerobic aquifer microcosms and demonstrated that the relative rates and extents of dechlorination ofPCE varied with the types of supplement substrates. Freedman and Gossett (1988) depicted that it was necessary to supply an electron donor to sustain reductive dechlorination of peE or trichloroethylene and showed that methanol was the most effective one, although hydrogen, formate, acetate, and glucose also served as electron donor.…”
Section: Resultsmentioning
confidence: 99%
“…/11 situ bioremediation is one of the progressive technologies for the remediation of contaminated groundwaters by stimulating the microflora with the addition of carbon and energy sources and trace mineral elements in place. Field and laboratory evidence suggest that the addition of auxiliary carbon and energy sources is necessary for the onset of the biodegradation of the trace-level anthropogenic organic compounds (DiStefano et aI., 1991;Doong and Wu, 1992b;Gibson and Sewell, 1992). Recent research has addressed the potential roles of the high concentration of the supplemental energy sources, such as acetate, methanol, and some short-chain organic acids and alcohols, on the dechlorination of polychlorinated biphenyls (PCBs) (Nies and Vogel, 1990), 2,4,5-T (Gibson and Suflita, 1990), chloroanilines (Kuhn et a/., 1990), and tetrachloroethylene (PCE) (Fathepure and Boyd, 1988;Bagley and Gossett, 1990;Gibson and Sewell, 276 1992).…”
mentioning
confidence: 99%